Simulation, implementation, and measurement of a complementary antenna - Chia, Lester Wei Jie (Nanyang Technological University, 2023)
Antenna plays an important role in wireless communication. The purpose of this study is the exploration and application of complementary antennas, a unique structure that seamlessly integrates a monopole and a slot. To begin, the fundamental knowledge behind monopole and slot antennas are explored, to provide a comprehensive understanding of its individual role and importance. Building on this knowledge, the study then transitioned into the integration of these two components - monopole and slot antenna, to design a 3D complementary antenna.